Cyathus lignilantanae sp. nov., a new species of bird’s nest fungi (Basidiomycota) from Cape Verde Archipelago - Martin, Maria P; Cruz, Rhudson H. S. F.; Dueñas, Margarita; Baseia, Iuri G.; Telleria, M. Teresa (Phytotaxa, 2015)
Cyathus lignilantanae sp. nov. is described and illustrated on the basis of morphological and molecular data. Specimens were collected on Santiago Island (Cape Verde), growing on woody debris of Lantana camara. Affinities with other species of the genus are discussed.